Kālam Khabar: A Study of Its Structure and Functions in Qur’anic Interpretation - haryanti Rusli; Mohamad Harjum; Dudung Abdullah (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Kalâm khabar is one of the essential elements of Qur’anic rhetoric that functions not only to convey information but also to serve various rhetorical purposes according to the context of the verses. This study aims to analyze the structure of kalâm khabar and its functions in the interpretation of the Qur’an. The research employs a qualitative approach using library research with content analysis of Qur’anic verses and balāġah literature. The findings reveal that the structure of kalâm khabar in the Qur’an is presented in various forms, namely ibtidâ’î, ṭalabî and inkârî, which are adapted to the condition of the mukhāṭab. Its functions include fâ’idah al-khabar, lâzim al- fâ’idah, as well as various rhetorical functions. The study concludes that understanding the structure and functions of kalâm khabar enriches Qur’anic interpretation and highlights the rhetorical beauty of the Qur’an. The implication of this study is to understanding the Qur’anic message more comprehensively.